Chemical exchange of labile protons by deuterium enables selective detection of pharmaceuticals in solid formulations. Issue 82 (27th September 2022) - Welton, Claire; Raval, Parth; Trébosc, Julien; Reddy, G. N. Manjunatha
Abstract : A solid-state 1 H– 2 H isotope correlation NMR spectroscopy (iCOSY) approach is introduced to detect low concentrations of deuterated drugs in pharmaceutical formulations. Abstract : Chemically assisted swapping of labile protons by deuterons is presented for amino acids, polysaccharides, pharmaceutical compounds, and their solid formulations. Solid-state packing interactions in these compounds are elucidated by 1 H– 2 H isotope correlation NMR spectroscopy (iCOSY). A minuscule concentration of dopamine, 5 wt% or ∼100 μg, in a solid formulation can be detected by 2 H NMR at 28.2 T ( 1 H, 1200 MHz) in under a minute.